Resource Potential of the Tana Basin with Particular Focus on the Bwathonaro Watershed, Kenya - Agwata, Jones (My University, 2006)
The Tana Basin of Kenya is one of the most important basins in the country comprising of several catchments that are endowed with diverse resources. The utilization of these resources is necessary to the development of the basin and the whole country. However, the way the various resources in the basin are used can have serious implications on the basin’s environment upon which the resources depend. Before resources in any basin can be put to use, it necessary and important to know the type of resources available in the basin and how use of the resources affects the basin or catchment. In this paper a general overview of the Tana Basin is provided and the resource potential in the Bwathonaro watershed, an important catchment in Meru North District in the upper parts of the basin, presented. The challenges of resource utilization in the watershed are examined and some of the interventions to the challenges suggested towards ensuring integrated and sustainable management of the resources in the watershed for continued development of the watershed and the entire basin.